Диагностика глубоких центров на границе пленка–подложка в тонкопленочных эпитаксиальных структурах GaAs - Gorev, N. B.; Kodzhespirova, I. F.; Privalov, E. N. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
A simple method for the determination of the concentration of vacant deep traps in the vicinity of the «film — substrate» interface is proposed. The method is based on determining the increase in the width of the conducting channel under extrinsic illumination from the shift of the inflection point in the capacitance-voltage curve. The reliability of the method is confirmed by measurement of the concentration of vacant deep traps in GaAs wafers with and without a buffer layer.